THE NEED TO OVERHAUL SCIENCE RESEARCH- CHALLENGES OF WASTED FUNDING AND IRREPRODUCIBLE RESEARCH - Bhaskar, Deepika (European Scientific Journal, ESJ, 2015)
Global science research involves finances to the tune of billions and millions of people. In 2010, the expenditure on Life Sciences research globally was US240 billion. Still one third of science information on the net is incorrect. 85% of investment in biomedical research is wasted due to inadequate reporting. Half of the published research cannot be replicated. The most striking findings have greatest chance of making it to the leading journals that impose high rejection rates to the tune of 90% of submitted manuscripts forcing scientists to exclude inconvenient data which may otherwise be significant. The time lag for translational research is an average 17 years with huge investments for research evidence to reach clinical practice. The way science research initiatives are chosen, designed, carried out, recorded, analysed, reported, regulated and published is under scrutiny. There is a dire need to redefine priorities and ways of conducting and reporting research in order to reduce waste and inefficiency in science research. A serious re-look is required into the kind of projects funded, systematic review of previous data, conduct, writing and publication of research.